Women and Girl Child Labour in the Bangle Industry of Hyderabad, India - Pande , Rekha (Studia Historiae Oeconomicae, 2023)
The present paper attempts to see the women and child worker in the old city of Hyderabad in the Bangle industry. Women make up a sizable portion of India’s labour force, yet they are paid less and have less secure jobs than men. As a result, many of these mothers choose to earn an income for their families by working from home. Women who work in the informal sector work with minimum pay and hence the girl child is an easy prey to assist the mother in supplementing the income and helping in the household chores so that more time is left to pursue the trade for an income. Our sample includes 100 women respondents and 150 girls. Being in the unregulated, home-based informal sector has made it challenging to organize the employees, leaving the bulk of bangle-makers in precarious positions both at work and at home. The increasing number of children, especially girls, who are taking part in the production of bangles is also a cause for alarm. It would appear that the piece rate method of payment and the fact that the work may be done from home encourage the participation of family members, including children, in the labour force.